Narrativas orais de sujeitos afásicos à luz da análise de discurso de linha francesa - Costa, Maria de Fátima Ferreira da (2006)
The vicissitudes on the use of language codes of aphasic subjects oblige the discourse analyst to understand the meanings of their speech. The objective of this study was to interpretate, according to French theory for discourse analysis, the reformulations that three aphasic subjects made on their oral narratives, emphasizing the meanings of hesitations, pauses and silences that these subjects attributed. Within this research, the author presented the study of aphasiology, neurolinguistics, narratives and their interpretations on the discourse of aphasic subjects, according to the French theory for discourse analysis. The first emphasis was the study of central nervous system and its language specific areas, which, once injured, oblige the subject to rediscover the ways to express and to understand whatever is said to him. Another aspect was the linguistic studies on language structure as well as on the performance of language flow. By joining the first and the second points of view, it was possible to elucidate a little more the language performance of aphasic subjects